Transformational Leadership Style in Primary Schools: Enhancing Teacher Engagement and Pupils’ Academic Performance in Lindi Region, Tanzania - Kayombo, Vicent Boniface; Matete, Rose Ephraim; Suru, Majiyd H (Papanda Publisher, 2025)
This study investigates the implementation of transformational leadership in primary schools within the Lindi Region of Tanzania, emphasizing on teacher’s engagement on enhancing Pupils academic performance. Grounded in pragmatism, the research employs a mixed-methods approach, integrating qualitative and quantitative data gathered through questionnaires and interviews, to provide a comprehensive understanding of leadership practices in educational settings. A total of 360 participants, including 356 primary school teachers and 4 key informants, were involved in the study, representing a diverse range of perspectives on leadership effectiveness. Findings revealed a noteworthy perception among educators regarding the role of head teachers in fostering a collaborative and motivating environment. A significant 75% of respondents acknowledge that transformational leadership principles, such as inspiring and empowering teachers, are effectively integrated into school management practices. However, despite these positive perceptions, a critical gap is identified in the practical implementation of teachers’ engagement and parental involvement, with only 37.36% of respondents strongly agreeing on the effectiveness of these efforts. Data analysis indicates that head teachers frequently engage in school activities and focus on motivating teachers, crucial for cultivating a culture of respect and collaboration. The findings further highlight the necessity of enhancing capacity building among school leaders to translate transformational leadership style ideals into practices. The study underscores the significance of ongoing professional development and the establishment of comprehensive frameworks that facilitate stakeholder engagement in school governance. Overall, the findings illustrate the transformative potential of effective leadership practices in primary schools in Lindi region and Tanzania as whole.